2008
DOI: 10.1111/j.1741-2358.2008.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between MRI evidence of degenerative condylar surface changes, induction of articular disc displacement and pathological joint sounds in the temporomandibular joint

Abstract: The articular disc motion to the condyle in the PBC group was smaller than in the ABC group irrespective of the configuration of the disc, even though there were no significant differences between the two types of bony changes in the disc position during jaw closing. The joint vibration analysis of the TMJ showed that joint sounds with a higher frequency were observed in the PBC group than in the ABC group. High energy levels needed to produce the higher frequencies (over 300 Hz) were observed only in the PBC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 14 publications
2
18
1
Order By: Relevance
“…AKERMAN et al studied the relationship between clinical and radiological TMJ findings in 101 patients with RA and found that although 80% of the TMJs that presented with crepitation also exhibited radiographic evidence of erosion, crepitation revealed a low sensibility in detecting joints with erosion, since half of the joints with erosion presented with either a click or no sound at all 1 . Lack of sounds in spite of joint damage may be a result of remodelling and adaptation of the articular surfaces 19 .…”
Section: Discussionmentioning
confidence: 99%
“…AKERMAN et al studied the relationship between clinical and radiological TMJ findings in 101 patients with RA and found that although 80% of the TMJs that presented with crepitation also exhibited radiographic evidence of erosion, crepitation revealed a low sensibility in detecting joints with erosion, since half of the joints with erosion presented with either a click or no sound at all 1 . Lack of sounds in spite of joint damage may be a result of remodelling and adaptation of the articular surfaces 19 .…”
Section: Discussionmentioning
confidence: 99%
“…17,29 Ogütcen-Toller 29 suggested that clicking and crepitation may be looked on as signs of an abnormal joint disorder, with clicking indicating anterior disc displacement with reduction and crepitation indicating progression from anterior disc displacement without reduction to degenerative arthritis. According to Honda et al, 30 pathological bone changes including erosion, osteophyte formation, and deformity are associated with joint sounds with a higher frequency.…”
mentioning
confidence: 99%
“…Sato et al [8] took MR images before and after arthroscopic lysis and lavage and found no correlation between joint effusion and the clinical condition after treatment. Some discussion has considered erosive cortical changes in the condyle to be an accurate finding with a high impact for patients presenting with TMJ pain and joint sounds [20,21]. Such a pathologic lesion in the condylar head increases joint friction, and it is conceivable that risk of pain and dysfunction in the joint increases.…”
Section: Discussionmentioning
confidence: 99%